Physicochemical and antioxidant profiling of fermented milk drinks - Chang, Yu Jie (2025)
Fermented dairy-based beverages have been consumed for centuries and continue to be widely popular in contemporary markets. Numerous brands of fermented milk drinks are commercially available, yet their physicochemical and antioxidant properties vary depending on the production process. This study aimed to analyse the physicochemical and antioxidant properties of selected commercially available natural flavoured fermented milk beverages produced by different food companies. The samples included three cultured milk drinks (Yakult®, Vitagen®, and Betagen) and three yogurt drinks (Farm Fresh®, Lactel, and Yobick). Physicochemical parameters, including pH, total titratable acidity (TTA), total soluble solids (TSS), and colour, were assessed, along with antioxidant properties, including total phenolic content (TPC), total flavonoid content (TFC), ferric reducing antioxidant power (FRAP), and DPPH radical scavenging activity (RSA). Data were analysed using nested analysis of variance (ANOVA) followed by Tukey's HSD test to determine significant differences (p≤0.05). Results indicated that Yakult® cultured milk exhibited the lowest pH (3.98±0.044) and the highest TTA (6.79±0.91), reflecting the highest acidity and a sour taste profile. Betagen cultured milk had the highest °Brix value (17.4±0.10), suggesting greatest degree of sweetness. Cultured milk drinks generally appeared darker and more yellowish, whereas yogurt drinks tended to be lighter and exhibited less yellow intensity. In terms of antioxidant properties, Farm Fresh® yogurt drink had the highest TPC (1.084±0.006) and TFC (5.148±0.071), indicating greatest phenolic and flavonoid content due to the presence of a greater number of probiotic strains. Lactel yogurt drink exhibited the highest FRAP (3012.50±12.37) and RSA (50.21±0.45), suggesting superior antioxidant activity attributed to its high protein content in fermented milk base. Fermentation conditions characterized by moderate acidity, the inclusion of acidproducing and multiple probiotic strains, and the use of a high-protein milk base were essential in order to produce fermented milk beverages with superior antioxidant quality.